Pengaruh Neuromuscular Electrical Stimulation Terhadap Peningkatan Kekuatan Otot Dorsalflexor Ankle Pada Penderita Stroke - Rachsanjani, A. Reza; , Totok Budi Santoso, S.Fis., MPH; , Umi Budi Rahayu, S.Fis.,Ftr.,M.Kes (2015)
Stroke represent cause handicap of first in the world. Most elementary problematik cover the trouble motorik able to result the paralysis of one of body side, abnormalitas tonus of muscle and trouble sensory to result the disparity sensibilitas, reseptor joint, feeling move and trouble coordinate. Physiotherapy of stroke so central in service rehabilitate the, NMES used to educate to return the muscle function, assisting contraction muscle, strengthening muscle, looking after a period of and energy burst the muscle of during immobilization old ones and to prevent the happening of atropi and muscle weakness of patient with the chronic disease. Target of this research to know the influence of Neuromuscular Electrical Stimulation make up strength of muscle dorsaflexor of patient stroke. This Research type is single case research by desain is A-B-A. Population in this research is natural patient stroke of weakness muscle of dorsalflexor ankle. Sampel is 4 respondents with the method of sampling intake that is purposive sampling. Technique analyse the data use the descriptive statistic with a purpose obtain the picture clearly about result intervence. Result of research indicate that there are positive influence of Neuromuscular Electrical Stimulation to improvement of muscle strength of dorsalflexor ankle of patient stroke after given by a therapy by 2 are program that are 2/2 and 2/4 frequency 100 Hz. Giving of TENS program 2/4 in the reality more effective than 2/2 to improvement of muscle strength of dorsalflexor ankle of patient stroke. Conclusion in this research there is positive influence of Neuromuscular Electrical Stimulation to improvement muscle strength of dorsalflexor ankle of patient stroke.